KETEPATAN PEMBERIAN MP-ASI: PENGARUH DUKUNGAN KELUARGA DAN KONTEKS BUDAYA: - - Dewi Sartika Siagian; Herliana Riska; Fania Nurul Khoirunnisa; Nasri Devi (JOMIS (Journal of Midwifery Science), 2025)
ABSTRACT Community habits can influence mothers' actions in providing MP-ASI before the baby is given MP-ASI. Apart from that, according to the mother, a crying baby shows that the baby is still hungry, so additional food must be given. This is one of the failures in providing exclusive breastfeeding to babies before they are more than 6 months old. Giving MP-ASI too early has short-term and long-term impacts. According to WHO, babies who receive complementary foods before the age of 6 months are 17 times more likely to experience diarrhea and 3 times more likely to develop upper respiratory tract infections (ARI) than babies who are exclusively breastfed and receive MP-ASI on time. The method used in this research is quantitative with a cross sectional design. The data used in this study is primary data obtained directly by distributing questionnaires to respondents. This research was conducted in the working area of ​​the Payung Sekaki Community Health Center, Pekanbaru City, Riau. The sample in this study was mothers who had babies aged 6-24 months with a total sample of 163 people. The aim of the research is to determine the influence of family support and cultural traditions on the accuracy of giving MP-ASI. The research results show that there is a relationship between family support and family traditions on the accuracy of providing MP-ASI with a P value <0.005. This shows that the provision of complementary foods is influenced by family support and cultural traditions.